PENGATURAN TALAK DAN ‘IDDAH (STUDI KOMPARATIF PRESPEKTIF FIKIH EMPAT MAZHAB DAN KOMPILASI HUKUM ISLAM (KHI)) - Hayati, Zakiyah (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
A happy  family is born  and  the inner  desire  of each  partner and  the individuals  who  are  in a family. But do not rule out the cherished goal, covenants they make together experiencing the shock  impacting on the creation of the marital discord,  disagreement, each  party still carries  each  ego  respectively. Therefore the  happy  marriage which  was  originally going to be cracks or divorce. With the divorce, the consequences are ‘Iddah. In the case of divorce and ‘Iddah arrangement was stipulated in Islamic law either globally or specifically (the four schools  of jurisprudence) and Islamic Law Compilation (KHI).The problems of this study was twofold: 1. How do the provisions of divorce and ‘Iddah according to the four schools of fiqh and Islamic Law Compilation  (KHI)? 2. How Relevance provisions of divorce and ‘Iddah according to the four schools of fiqh and Islamic Law Compilation  (KHI) In the era of modern society ?.The method used in this compiler is a comparative descriptive method that describes the view of the four schools  of jurisprudence about  the divorce arrangements and ‘Iddah then linked to Islamic Law Compilation (KHI) in Indonesia. Type of research is the research library (library research), whereas the approach used  in this study is a normative approach. In analyzing the data  compiler using the deductive method with deductive mindset is to analyze  the problem of divorce  and  ‘Iddah in general  and  then  withdrawn on dissent in the Four Schools  of Jurisprudence about  the  divorce  arrangements and  ‘Iddah.From the  analysis  that has  been done  in this study setting divorce  and ‘Iddah contained in Jurisprudence four schools  and Islamic Law Compilation  (KHI) do not have much difference, and with the relevance of Jurisprudence four schools  and Islamic Law Compilation  (KHI) portion  of provisions divorce and ‘Iddah that has prevailed  still be valid in the era of modern society